2020
DOI: 10.1007/s00204-020-02688-4
|View full text |Cite
|
Sign up to set email alerts
|

ROS-induced oxidative damage in lymphocytes ex vivo/in vitro from healthy individuals and MGUS patients: protection by myricetin bulk and nanoforms

Abstract: We investigated the protective role of myricetin bulk and nanoforms, against reactive oxygen species (ROS)-induced oxidative stress caused by hydrogen peroxide and tertiary-butyl hydro peroxide in lymphocytes in vitro from healthy individuals and those from pre-cancerous patients suffering with monoclonal gammopathy of undetermined significance (MGUS). The change in intracellular reactive oxygen species was measured once cells were treated with myricetin bulk forms and nanoforms with and without either hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
6
1
Order By: Relevance
“…In our previous study (Akhtar et al 2020a , b ), we found no relationship among the confounding factors (age, ethnicity, smoking) regardless of the treatment groups and these factors also do not seem to be contributing in this study towards DNA damage.…”
Section: Resultscontrasting
confidence: 48%
See 3 more Smart Citations
“…In our previous study (Akhtar et al 2020a , b ), we found no relationship among the confounding factors (age, ethnicity, smoking) regardless of the treatment groups and these factors also do not seem to be contributing in this study towards DNA damage.…”
Section: Resultscontrasting
confidence: 48%
“…The effects of MYR B and MYR N on the viability of healthy lymphocytes were compared to those of the untreated group. Neither of the concentrations of MYR B and MYR N reduced viability less than 80% in the healthy group (Akhtar et al 2020a , b ). However, MYR B and MYR N at 40 µM reduced the viability to 68% and 51%, respectively, after 48 h of treatment in lymphocytes from multiple myeloma patients (shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The suspensions were stored in amber glass bottles at 4 ℃ for the research duration. The concentrations of myricetin bulk (MYR B) and NP (MYR N) forms, used for this research study were 10 µM and 20 µM, respectively (data used from previous study) (Akhtar et al 2020 ). The concentration of PhIP used throughout the study was 100 µM.…”
Section: Methodsmentioning
confidence: 99%